A new species, Bryobrothera tambuyukonensis (Daltoniaceae, Bryopsida), from Sabah, Borneo Island - Akiyama, Hiroyuki; Suleiman, Monica (Phytotaxa, 2015)
We report a new species Bryobrothera tambuyukonensis, based on the specimens collected in Sabah, Borneo Island. Phylogenetic analyses with plastid (rps4 and trnL-F) and mitochondrial (nad5) genes along with a number of morphological features (for example, undulate lamina, oblong-lanceolate leaves with a single strong costa reddish brown in color, and thick-walled and porose laminal cells) confirmed its distinctiveness from B. crenulata and also close relationship to the elimbate group comprised of Adelothecium bogotense and Benitotania elimbata.